You're a Damned Dumb!" Political Trolls of Iraqi Female Parliamentary Members on X Platform - Al-Zubaidi, Prof. Nassier A. G. Al-Zubaidi; Jasim, Assist. Prof. Tahani Awad Jasim (Sulaimani Journal for Humanities, 2026)
With the spreading unchecked growth of access to social media worldwide, the internet has given birth to the incessant phenomenon of cyber trolling. Cyber trolling is often characterized as aggressive behaviors with negative impacts on online communication. The present research investigated the pragmatic resources and choices of trolling behavior used by Iraqi users against Iraqi female parliamentary members (MPs) on X platform. To achieve the research objectives, a purposive sampling technique was used for the collection of data. The data were collected from X platform accounts of six Iraqi female MPs representing different political stands and demographics. The analysis involved identifying, classifying and counting actual tokens of trolling forms, impoliteness strategies, and trolled speech acts across data sets from the X platform. The analysis revealed that Iraqi users of X platform use provocation and ideological misalignment as the most frequent forms of cyber trolling with Iraqi female MPs. As for impoliteness strategies, Iraqi users employ negative face-oriented strategies more frequently than positive face-oriented strategies. Besides, direct trolled speech acts commonly employed by Iraqi users when trolling Iraqi female MPs. Finally, based on the research findings, a number of conclusions, implications and recommendations are presented
Keywords: Political trolls; speech acts; impoliteness; X platform; Iraqi female MPs